2013
DOI: 10.2478/acph-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antibacterial and cytotoxic activity evaluation of hydroxyurea derivatives

Abstract: Hydroxyurea and its derivatives exhibit versatile biological activities. Hydroxyurea is currently used in the treatment of various neoplastic and non-neoplastic diseases such as cancer, sickle cell anemia and HIV (1). Derivatives of hydroxyurea were found to inhibit matrix zinc metaloproteinases (MMP), urease, carboanhydrase, carboxypeptidase, cyclooxygenase and 5-lipooxygenase. Early experiments on antibacterial properties and effects on tumor cell lines of hydroxyurea and low molecular mass derivatives were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The importance of isocyanates is exemplified by the greater than 4000 commercially available reagents and the millions of tons produced and used every year. Heteroatom-substituted isocyanates, however; are considerably scarcer, with less than 100 publications relating to nitrogen-substituted isocyanates ( N -isocyanates) and less than 20 relating to O -isocyanates. , O -Isocyanates are particularly difficult to manipulate due to their propensity to trimerize or to undergo Lossen rearrangements through cleavage of the N–O bond. , Until recently, there was only one reported example of controlled reactivity of an O -isocyanate, which was formed in situ from precursors containing an imidazole blocking (masking) group. , This pioneering work by BMS chemists showed that trimerization can be avoided through in situ isocyanate formation, likely by controlling the concentration of O -isocyanate available. However, only the reactivity of BnO–NCO precursors was studied, and limitations to the reaction scope were present.…”
mentioning
confidence: 99%
“…The importance of isocyanates is exemplified by the greater than 4000 commercially available reagents and the millions of tons produced and used every year. Heteroatom-substituted isocyanates, however; are considerably scarcer, with less than 100 publications relating to nitrogen-substituted isocyanates ( N -isocyanates) and less than 20 relating to O -isocyanates. , O -Isocyanates are particularly difficult to manipulate due to their propensity to trimerize or to undergo Lossen rearrangements through cleavage of the N–O bond. , Until recently, there was only one reported example of controlled reactivity of an O -isocyanate, which was formed in situ from precursors containing an imidazole blocking (masking) group. , This pioneering work by BMS chemists showed that trimerization can be avoided through in situ isocyanate formation, likely by controlling the concentration of O -isocyanate available. However, only the reactivity of BnO–NCO precursors was studied, and limitations to the reaction scope were present.…”
mentioning
confidence: 99%
“…In contrast to N-benzyloxyisocyanate, no corresponding reactions were observed for methoxyisocyanate and ethoxyisocyanate, i.e., the decomposition products of the structural analogues 1-(N-methoxycarbamoyl) benzotriazole and 1-(N-ethoxycarbamoyl) benzotriazole. Findings described in this work could be useful in the preparation of new and modifi cation of the existing compounds, particularly in the light of the recently confi rmed biological effects of these compounds (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…6), thus confi rming the proposed formation of N,N',N''-tribenzyloxyisocynauric acid during heating of 1-(Nbenzyloxycarbamoyl) benzotriazole. Additional confi rmation is the presence of peaks at 1740, 1402, 1197, 1001 and 905 cm -1 , characteristic for N,N',N''-tribenzyloxyisocynauric acid (11,12).…”
Section: Ir Spectramentioning
confidence: 99%
See 2 more Smart Citations